How Do Public Debt Cycles Interact with Financial Cycles? - Poghosyan, Tigran (Washington, D.C. : International Monetary Fund, 2015)
We employ a duration model to study determinants of public debt cycles in 57 advanced and emerging economies over the 1960-2014 period, with a particular focus on the impact of financial cycles. The results suggest that the association between financial and debt cycles is asymmetric. Debt expansions preceded by overheating in credit and financial markets tend to last longer than other expansions, but there is no significant association between financial cycles and debt contractions. There is strong evidence of duration dependence in both phases of the cycle, with the likelihood of expansions and contractions to end increasing with the length of their respective spells. Higher initial level of debt increases the spell of contractions (persistence of adjustment effort hypothesis) and reduces the spell of expansions (debt sustainability hypothesis). This result is robust to the inclusion of global factors, openness, political stability, and debt crisis indicators as additional controls.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet